Pengembangan Media Pembelajaran Teknik Dasar Terintegrasi Fisik Permainan Tenis Lapangan Berbasis Android - Syahriadi Syahriadi; Ardiah Juita; wedi s (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2025)
This research aims to develop a learning medium for basic tennis techniques, integrated with physical training, using an Android application. This media development was carried out as a solution to the needs of modern sports learning that demands innovation, accessibility, and effectiveness in material delivery. The subjects in this study were 30 sports coaching education students from the 2025 intake. The research method employed was Research and Development, utilizing the ADDIE development model, which encompasses the stages of analysis, design, development, implementation, and evaluation. The resulting product is an Android application containing material on basic tennis techniques, such as forehands and backhands, and is equipped with physical training models to support the improvement of students' motor skills. The development results indicate that the learning medium is deemed feasible based on assessments by material experts, media experts, and student responses, which indicate an increase in understanding and skills in basic tennis techniques integrated with physical condition after using the medium. Therefore, this learning medium can be an alternative in the teaching process of sports, particularly tennis, and has the potential for wider implementation in various learning activities.